Assess the Knowledge Regarding Usage of Plastic Leading to Cancer Risk and Their Preventive Measures Among House Wives in Selected Area Vaniyamkulam - Zaina Jose Elizabeth; Krishna Prabha; Blessy Biju; Devika S.; Divya Johny; Divya K.K.; Fathima Salam (International Journal of Oncological Nursing and Practices, 2024)
This study explores the level of awareness among housewives in Vaniyamkulam about the potential cancer risks associated with the use of plastic materials in households, along with their knowledge of preventive measures. The proliferation of plastic usage in daily life has raised significant health concerns, particularly its potential to release carcinogenic compounds such as bisphenol A and dioxins, which can leach into food and beverages. Given the critical role housewives play in managing domestic environments, their awareness and practices are pivotal in mitigating health risks. A cross-sectional survey was conducted involving 200 housewives from Vaniyamkulam, using a structured questionnaire to assess their knowledge about the types of plastics, associated cancer risks, and the preventive strategies they employ. The data were analyzed to correlate the level of awareness with demographic variables such as age, education, and socioeconomic status. Preliminary results indicate a moderate level of awareness regarding the health implications of using certain plastics; however, detailed knowledge about specific carcinogens and safer alternatives remains low. Many participants were unaware of the coding system of plastics and the significance of recycling symbols, which are crucial for identifying safer plastic options. Moreover, preventive practices such as using alternatives to plastic containers for food storage and heating were sporadically implemented, influenced heavily by socioeconomic factors. The findings suggest an urgent need for targeted educational programs that could enhance understanding of the health risks posed by certain plastics and promote safer practices. Such initiatives should focus on disseminating information about the identification of safer plastics, the importance of avoiding plastic exposure to heat, and encouraging the adoption of non-plastic alternatives in household settings. This study underscores the necessity of integrating health education into community outreach programs, particularly in semi-urban areas like Vaniyamkulam, to combat the latent health risks of everyday materials and to empower housewives in their role as primary caretakers of family health.
Keywords: Plastic usage; Preventive measures; Vaniyamkulam; cancer risk awareness; housewives